Case Report: Toxic tubulointerstitial nephropathy with lipofuscin deposition – the potential cause of occupational Bisphenol-A exposition - László Bidiga; Tamás Csonka; Gábor Méhes; Csilla Markóth; Dávid Hutkai; János Mátyus (Pathology and Oncology Research)
This case study delves into the link, between exposure to Bisphenol A (BPA) and kidney issues filling a gap in human focused research found in studies. The individual, a 72-year man with a history of BPA exposure in a plastics manufacturing facility experienced a gradual decline in kidney function over 18 months. Medical tests showed kidney disease with a buildup of lipofuscin in renal tubular cells upon examination. This discovery suggests a connection between BPA exposure and kidney damage underscoring the need for investigation. The lack of human based evidence highlights the importance of research to understand the toxic effects of BPA on the kidneys. In addition, to its implications this case emphasizes the importance of improving safety protocols and raising awareness among healthcare professionals in relevant work environments to reduce potential health risks associated with BPA exposure.